MS ISO 9001 2015 Teaching and Learning Internal Audit Series 2 and AQMS Baseline Audit Visit to PSM UMPSA - Siti Zanariah, Satari (Pusat Sains Matematik (PSM), 2024)
An MS ISO 9001: 2015 (Teaching and Learning) Internal Audit Series 2 and Academic Quality Management System (AQMS) Procedure Baseline Audit visit to the Centre for Mathematical Sciences (PSM) was conducted on June 6, 2024.